닥나무로 제조된 우드세라믹의 성질 -탄화온도의 영향 - 변희섭; 황교길; 이동환; 황정우; 오승원; Hee-Seop Byeon; Kyo-Kil Hwang; Dong-Hwan Lee; Jung-Woo Hwang; Seung-Won Oh (농업생명과학연구, 2010)
인피섬유로 한지를 제조하고 남은 닥나무 목질부를 고부가치화 하기 위하여 닥나무 목질부로 제조된 파티클보드를 이용하여 탄화온도 변화에 따른 닥나무재료 우드세라믹을 제조하여 물성을 검토하였다. 밀 도, 휨강도성능, 브리넬 경도, 압축강도 등은 탄화온도가 증가할수록 증가하였으며 밀도와 휨강도성능, 경도, 압축강도사이에는 유의성이 인정되는 밀접한 상관관계를 나타내었다. This study was carried out to investigate the properties of woodceramics made from woody part of Broussonetia Kazinoki at different carbonizing temperatures of 600℃, 800℃, 1000℃ and 1200℃. The physical and mechanical properties increased with increasing carbonizing temperature. The highest mean values of density, bending strength, Brinell hardness and compressive strength were 0.62 g/cm 3 , 79 kgf/cm 2 , 203 kgf/cm 2 and 129 kgf/cm 2 , respectively. There were close correlations between density and bending strength, Brinell hardness and compressive strength and MOE and MOR.